MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS XI IPA 2 SMA PGRI 4 BANJARMASIN PADA KONSEP SISTEM KOLOID MELALUI MODEL PROBLEM BASED LEARNING - Rusmina Wati; Rusmansyah Rusmansyah; Arif Sholahuddin (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract. A study concerning the use of Problem Based Learning Model in colloidal systems matter. This study aims to improve (1) Fitness teacher in class XI IPA 2 SMA Negeri 4 Banjarmasin in colloidal systems, through the application of the model of Problem Based Learning, (2) Activity teacher in class XI IPA 2 SMA Negeri 4 Banjarmasin in colloidal systems, through the application of Problem Based learning Model, (3) critical thinking skills of students of class XI IPA 2 SMA Negeri 4 Banjarmasin in colloidal systems through the application of the model of Problem Based Learning, (4) the results of students of class XI IPA 2 SMA Negeri 4 Banjarmasin in colloidal systems through the application of the model problem Based Learning. The method used is the PTK with 2 cycles. Research subjects were students of class XI IPA 2 SMA Negeri 4 Banjarmasin by the number of students 30 people consisting of 22 women and 8 men. Learning outcomes data were collected using a test of learning outcomes, the data collected using the critical thinking skills and essay test activity data and student teachers using observation sheets. Data were analyzed qualitatively. The results showed that the activity of teachers in applying the model of Problem Based Learning in the learning process increases every meeting. Activities of students in the learning process increases every meeting. Problem Based Learning model application can improve students' critical thinking abilities of 59.96% in the first cycle to 75.6% in the second cycle. Application of Problem Based Learning Model to improve the mastery of cognitive learning outcomes of students ie from 64.83% in the first cycle, and 83.67% in the second cycle.Keywords: Problem Based Learning, learning outcomes, critical thingking skill, colloidal systems.